2018
DOI: 10.18535/ijsrm/v6i3.el03
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Chinhoyi University of Technology’s staff and students regarding the Communication Skills course

Abstract: This study explores the myriad of perceptions, perspectives, attitudes, approaches and conceptions about the module Communication Skills (CUACE101) which is a campus-wide compulsory course taught to all Chinhoyi University of Technology first year first semester (1.1) students. The motivating factor for this study has been an endless debate on the merits of the course to a university curriculum whose niche and mandate is predominantly technology-oriented, hence the need to establish the rationale for a communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In a study conducted by Nembaware (2018), the researcher prepared a program related to communication skills at a state university in Zimbabwe and the results of the study showed significant effects on students. Therefore, it can be determined that there is no significant difference between the communication skills according to the grade levels of university students.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Nembaware (2018), the researcher prepared a program related to communication skills at a state university in Zimbabwe and the results of the study showed significant effects on students. Therefore, it can be determined that there is no significant difference between the communication skills according to the grade levels of university students.…”
Section: Resultsmentioning
confidence: 99%